Acid Mine Drainage and Heavy Metals Contamination of Abandoned and Active Mine Site at Old REPAS Dam in Bentong Pahang - Syed, Ali Haider (2018)
AMD stands for Acid Mine Drainage. AMD results from the mining activities involved during mineral exploration. When minerals interact with each other in the presence of atmospheric oxygen and water AMD is the end product. AMD also accumulates from the weathering of sulphide minerals through the process of oxidation and hydrolysis. This case study was being carried out for the investigation of the occurrence of Acid Mine Drainage (AMD) and contamination of the heavy metals in the active and abandoned mining sites in Bentong, Pahang. This case study deals with the traces of heavy metal toxins found in the water bodies causing the discoloration of the water catchment, downstream of the Old Repas dam. This discoloration of water proved the occurrence of AMD which is a very bad pollutant. To get a better understanding of the situation, site reconnaissance and survey were carried out to examine those area closely that have been affected by AMD. Two different sampling points were recognised which had traces of AMD contamination. Water testing and sampling were to be carried on these particular sampling points. Four in-situ parameters and five heavy metals were selected for sampling. These parameters included PH of water, dissolved oxygen content. Total dissolved solids and Ammoniacal Nitrogen while the heavy metals included Zinc, Lead, Tin, Mercury and Arsenic. A total of four samples were collected on two different sampling points and on two different sampling days. Sampling was carried out, these parameters were measured and surface water with sediments were also collected and analysed for heavy metals. Based on the investigations done during this project, these sampling points had acidic PH values which indicate the occurrence of the Acid Mine Drainage, which had been a major find in this case study. During the Heavy Metal analysis concentration of Pb, Sn, Hg, As & Zn was observed to exceed the allowable standard limits for treated water by the Malaysian Ministry of Health. I concluded this with the believe that there was an urgent need for appropriate treatment of this site to prevent further environmental deterioration.